The State, Schooling and Identity : Diversifying Education in Europe - Kantasalmi, Kari; Holm, Gunilla (Springer Singapore : Imprint: Palgrave Macmillan, 2017)
This book offers insights into the nation-state and education relationship by problematizing and analyzing the assumed straightforwardness of the role of education and schooling by placing the issue in very contemporary contested nation-state structures like Scotland, Catalonia, Ukraine and Belgium. These conflict situations and contested power relations are in a way some of Europe's internal North-South struggles. In addition, the particular Nordic North-South example of the Saami with their status as indigenous people recognized in international law is viewed in terms of their educational struggle for better consideration of their cultural features in Saami land crossing the Nordic states. The book focuses on the Nordic countries, often viewed as globally exemplary in their educational arrangements, but casts deeper insight into Nordic education and points to problematic schooling issues in Northern Europe. This volume presents somewhat unexpected views on European educational arrangements with regard to the European growing diversity.
Keywords: Social sciences.; International education.; Comparative education.; Educational sociology.; Education and sociology.; Sociology, Educational.; Education and state.; elektronické knihy; electronic books